Tipologi Fatwa Kentongan: Studi Naskah Ḥukm al-Nāqūs - Abror, Muhamad; Nasrulloh, Sibli (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
In the early twentieth century, Traditionalist and Reformist Muslims in Indonesia often held conflicting views on religious traditions. However, the manuscript Ḥukm al-Nāqūs reveals a notable exception: in the case of the kentongan (wooden slit drum), both camps arrived at the same legal conclusion despite their divergent ideological frameworks. This study aims to examine the similarities and differences in istidlāl (legal reasoning) employed by the two groups in responding to religious rituals that have undergone acculturation with local culture, particularly the use of the kentongan as a call to prayer. Employing a qualitative, library-based research methodology, the study draws on the primary source of the Ḥukm al-Nāqūs fatwa manuscript, held in the Langitan Islamic Boarding School, Tuban, along with relevant secondary literature from early twentieth-century Islamic discourse. The research adopts a philological approach enriched by intertextual analysis, socio-intellectual history, and Islamic legal hermeneutics. The findings demonstrate that while Traditionalists anchor their legal reasoning in the authority of classical scholars, and Reformists prioritize direct reference to the Qur’an and Hadith, both may reach similar legal verdicts under specific conditions. This convergence suggests that ideological common ground can emerge when both traditions are oriented toward primary Islamic texts. The study contributes a novel analytical typology of fatwas through the lens of a single local manuscript, highlighting an unexpected legal convergence between two competing streams of Islamic thought in early twentieth-century Indonesia.